BRACU new campus development project construction schedule (September.2020-December.2020) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the construction schedule from September, 2020 to December, 2020 of BRACU new campus project.